Metabolic Response of “Candidatus Accumulibacter Phosphatis” Clade II C to Changes in Influent P/C Ratio - Welles, Laurens; Abbas, Ben; Sorokin, Dimitry Y.; Lopez-Vazquez, Carlos M.; Hooijmans, Christine M.; van Loosdrecht, Mark C. M.; Brdjanovic, Damir (Frontiers in Microbiology, 2017)
The objective of this study was to investigate the ability of a culture highly enriched with the polyphosphate-accumulating organism, 'Candidatus Accumulibacter phosphatis' clade IIC, to adjust their metabolism to different phosphate availabilities. For this purpose the biomass In six different experimental phases, the biomass was cultivated in a sequencing batch reactor with acetate and exposed to at different phosphate/carbon influent ratios during six experimental phases. Activity tests were conducted to determine the anaerobic kinetic and stoichiometric parameters as well as the composition of the microbial community. Increasing influent phosphate concentrations led to increased poly-phosphate content and decreased glycogen content of the biomass. In response to higher biomass poly-phosphate content, the biomass showed higher Faster active biomass specific phosphate release rates were observed as biomass poly-phosphate content increased. Together with the phosphate release rates, acetate uptake rates also increased up to an optimal poly-phosphate/glycogen ratio of 0.3 P-mol/C-mol at which the organisms were most competitive. At higher poly-phosphate/glycogen ratios (obtained at influent P/C ratios above 0.051 P-mol/C-mol)ratios, the acetate uptake rates started to decrease. The stoichiometry of the anaerobic conversions clearly demonstrated a metabolic shift from a glycogen dominated to a poly-phosphate dominated metabolism as the biomass poly-phosphate content increased. FISH and DGGE analyses confirmed that no significant changes occurred in the microbial community, suggesting that the changes in the biomass activity were due to different metabolic behavior, allowing the organisms to proliferate under conditions with fluctuating phosphate levels.